Unleashing the Pygmalion's nudge: The roles of leadership styles and leader expectations in driving employees' pro-environmental behaviors - Farrukh, Muhammad; Rafiq, Muhammad; Karatepe, Osman M.; Raza, Ali (Elsevier Sci Ltd, 2025)
Given that employees' pro-environmental behaviors (PEB) play a critical role in achieving sustainability goals, we utilized a mixed methods approach to explore the factors that may foster their PEBs. In view of the qualitative findings, we developed a conceptual model that examined green goal clarity as a mediator of the effects of green authentic and green servant leadership styles. The model investigated leader expectations of their followers (the Pygmalion effect) as a moderator of the impacts of these leadership styles on PEB, and the moderating role of environmental passion is investigated on the link between green goal clarity and PEB. Results suggest that the conceptual model developed in this study is viable, and all hypotheses are supported based on data gathered from hotel employees. Our research contributes to the literature on leadership styles and employee PEB, providing insights for practitioners and scholars seeking leadership strategies to promote and accomplish environmental sustainability goals.
Keywords: Environmental passion; Green authentic leadership; Green goal clarity; Green servant leadership; Hospitality industry; Pro-environmental behavior; The Pygmalion effect